2013
DOI: 10.4103/0300-1652.126288
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic dysfunction in sickle cell anaemia and its correlation with QT parameters

Abstract: Background:Abnormalities of QT parameters together with cardiac autonomic neuropathy (CAN) confer significant risks of cardiac morbidity and mortality in patients with diabetes mellitus. We questioned whether or not CAN influences occurrence of QT interval prolongation and dispersion in patients with sickle cell anaemia (SCA).Materials and Methods:Forty stable adult sickle cell patients with 44 healthy haemoglobin AA controls were studied. Baseline electrocardiograms were obtained and cardiovascular autonomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Prolonged and shortened QT C on ECG are both known risk factors for sudden cardiac death. 27 , 28 Although, the exact mechanism of prolonged QT C interval in sudden cardiac deaths in individuals with SCA is largely unknown, it is speculated that chronic anaemia and associated sub-acute cardiac ischaemia may be associated with ventricular repolarisation defects, which ultimately prolong QT C intervals. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Prolonged and shortened QT C on ECG are both known risk factors for sudden cardiac death. 27 , 28 Although, the exact mechanism of prolonged QT C interval in sudden cardiac deaths in individuals with SCA is largely unknown, it is speculated that chronic anaemia and associated sub-acute cardiac ischaemia may be associated with ventricular repolarisation defects, which ultimately prolong QT C intervals. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Autonomic dysfunction and QT interval duration were correlated in patients with sickle cell anemia, suggesting significant clinical implications. The presence of hypoxia due to chronic anemia and cardiac autonomic neuropathy, with unopposed sympathetic activation and abnormalities of ventricular repolarization, predisposes to ventricular electrical instability and increased arrhythmia risk [ 100 ]. Several foci of old and new degeneration in the sinus and atrioventricular node and His bundle, fibrosis, and fibromuscular dysplasia affecting small coronary arteries were revealed by postmortem studies in patients with sickle cell anemia, responsible for electrical instability [ 102 ].…”
Section: Cardiovascular Consequences Of Hereditary Forms Of Anemiamentioning
confidence: 99%
“…Kolo observed that Mean corrected QT (QTc) in sickle cell patients was significantly higher than the mean of controls. Similarly, mean QT dispersion (QTcd) was higher in the former than in the latter; the study showed that cardiac autonomic neuropathy is a risk factor for abnormalities of QT parameters in SCA and both may be harbinger for cardiac death [9].…”
Section: Introductionmentioning
confidence: 82%
“…SCD in its homozygous form has been linked with higher risk of ventricular arrhythmias and sudden death [9]. This study evaluates some of the risk factors…”
Section: Discussionmentioning
confidence: 99%